Has Reflective Practice Done More Harm than Good in Teacher Education? - Russell, Tom (Phronesis, 2013)
Why do we emphasize reflective practice so extensively in pre-service teacher education? What evidence do we have that frequent references to reflection are improving the quality of the teachers we prepare for certification and careers in teaching? Whatever reflection and reflective practice are, they are not ends in themselves; hopefully, they are means to the end of better teaching practices and better learning by students in schools. In this article I explore reflection and reflective practice from several perspectives, including my personal experiences as a teacher educator working with individuals preparing to become teachers of physics. The question asked in the title captures my fear that the ways teacher educators have responded to and made use of the concepts of reflection and reflective practice may be doing more harm than good in pre-service teacher education. To begin, I consider teacher education practices before and after the arrival of the term reflective practice. I then consider elements of Schön’s (1983) work and review five articles about reflective practice in teacher education; this is not a formal literature review, but rather an effort to show how virtually every article about reflective practice seems to be driven by its author’s personal perspective. The article continues with personal interpretations and illustrations and concludes with five generalizations about teacher education practices that indicate that much more work needs to be done if references to reflection are to do more good than harm in preservice teacher education programs.